Atherosclerotic risk factors and risk of myocardial infarction and venous thromboembolism; Time-fixed versus time-varying analyses. The Tromsø Study - Småbrekke, Birgit; Balteskard Rinde, Ludvig; Hindberg, Kristian; Mathiesen Hald, Erin; Vik, Anders; Wilsgaard, Tom; Løchen, Maja-Lisa; Njølstad, Inger; Mathiesen, Ellisiv B.; Hansen, John-Bjarne; Brækkan, Sigrid Kufaas (PLOS ONE, 2016)
Source at https://doi.org/10.1371/journal.pone.0163242. Background: Single measurements of modifiable risk factors may underestimate associations with outcomes in cohorts. We aimed to compare risk estimates of myocardial infarction (MI) and venous thromboembolism (VTE) by atherosclerotic risk factors during long follow-up using time-fixed analyses without and with correction for regression dilution and time-varying analyses. Methods: The study included 5970 subjects enrolled in the fourth survey of the Tromsø Study (1994/95). Blood pressure, lipid levels, body mass index (BMI), diabetes and smoking status were measured at baseline, and subjects still alive at the fifth (2001/02, n = 5179) and sixth (2007/08, n = 4391) survey were re-measured. Incident events of MI (n = 714) and VTE (n = 214) were recorded until December 2010. Time-fixed and time-varying Cox regression models were used to estimate hazard ratios (HR) for MI and VTE adjusted for age and sex. Results: Variations in BMI, blood pressure and lipid levels were small, and did not alter the risk estimates when time-varying analyses were compared to time-fixed analyses. For MI, variables that changed considerably over time yielded the greatest changes in risk estimates (HR for smoking changed from 1.80 (95% CI 1.55–2.10) to 2.08 (95% CI 1.78–2.42)). For VTE, only BMI was associated with increased risk in both time-fixed and time-varying analysis, but the risk estimates weakened in the time-varying analysis. Correction of time-fixed HRs with Rosner´s method tended to overestimate risk estimates compared to time-varying analysis.